A Christmas horror story [videorecording (DVD)] - Buza, George; Shatner, William (Image Entertainment, 2015)
Interwoven stories that take place on Christmas Eve, as told by one festive radio host: A family brings home more than a Christmas tree, a student documentary becomes a living nightmare, a Christmas spirit terrorizes, and Santa slays evil.